1993
DOI: 10.1265/jjh.48.746
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Readability between Liquid Crystal Displays and Cathode-Ray Tubes.

Abstract: Flat-panel displays, especially liquid crystal displays (LCDs), are almost universally used today. Do LCDs assure better readability than cathode-ray tubes (CRTs)? Two experiments were carried out to determine which type of display is better using a newly developed device. Four types of displays were tested; negative and positive CRTs, and LCDs with and without backlighting. Variables were the type of display, age, and gender. At first, analyses of readability using eye movements were conducted.Middle-aged sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Miyao, Hacisalihzade, Allen, et al [3] indicated the need for higher height for CRTs with low resolution. Character readability differs between the CRT and LCD [4,17]. The visual angle of 20-22' corresponds to an assumed character height of 2.9-3.2 mm at a VD of 50 cm in VDT work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyao, Hacisalihzade, Allen, et al [3] indicated the need for higher height for CRTs with low resolution. Character readability differs between the CRT and LCD [4,17]. The visual angle of 20-22' corresponds to an assumed character height of 2.9-3.2 mm at a VD of 50 cm in VDT work.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies on the readability or legibility of printed characters and characters on cathode ray tubes (CRT) or liquid crystal displays (LCD) of computers [1,2,3,4,5,6,7], and recommended character sizes have been standardized in terms of sign displays and video display terminal (VDT) work [8,9,10,11]. The results of these studies are useful in evaluating the qualities of displays and estimating optimal character sizes for each type of display.…”
Section: Introductionmentioning
confidence: 99%
“…Various forms of¯atpanel displays are being used increasingly as an alternative to conventional Cathode Ray Tube (CRT) monitors. However, such displays still account for a small proportion of the market and there is relatively little information about eye problems associated with their use (Miyao et al, 1993). For these reasons, this paper is mainly concerned with the visual ergonomics of conventional CRT-based VDTs.…”
Section: The Nature Of Vdt Displaysmentioning
confidence: 99%
“…The relationships between dark screens and visual accommodative load have previously been studied. Miyao et al 17) measured and calculated the focusing speed (the 90 percent maximum amplitude of accommodation from a distant poster to the computer monitor, divided by time spent). They found that even young subjects had lower focusing speeds when they looked at non-backlit dark LCDs than at other bright displays such as cathode ray tubes (CRTs) or backlit LCDs (p<0.05, Kruskal-Wallis test).…”
Section: Discussionmentioning
confidence: 99%